The Impact of Heavy Metal Fe, Zn, and Cu in Water and Sediment on the Histopathology of Gills and Liver of Mullet Fish (Crenimugil seheli) at Kamal Beach, Madura Strait - Kharisma Nuria Fitri; Muhammad Musa; Uun Yanuhar (Postgraduate, University of Mataram, 2024)
Kamal Beach in the Madura Strait is suspected to have experienced heavy metal contamination due to ship recycling industry activities. Heavy metals have a negative impact on the aquatic environment, aquatic biota and even humans. This study aims to analyze the impact of heavy metal content in Kamal Beach, especially heavy metals Fe, Zn, and Cu as heavy metals found in the region on the histopathological aspects of the gill and liver organs of aquatic biota, namely mullet fish (Crenimugil seheli). The levels of heavy metals Fe, Zn, and Cu were analyzed using the AAS (Atomic Absorption Spectometry) method in accordance with SNI 6989.4:2009. Hiatopathological analysis of the gill and liver organs was carried out using the scoring method where from the results of the analysis it was known that the damage that occurred in the gill organs was in the form of edema, hyperplasia, lamellar fusion, and necrosis while damage to the liver organs included degeneration, necrosis, and congestion. Damage to the gill and liver organs of mullet fish is caused by the high content of Zn and Cu in water and sediment.